2014
DOI: 10.1080/19392206.2014.909246
|View full text |Cite
|
Sign up to set email alerts
|

Boko Haram Insurgency and the Widening of Cleavages in Nigeria

Abstract: The Boko Haram terrorist group's philosophy and activities have been subjected to different interpretations among the Nigerian populace. Such interpretations follow traditional lines of ethnic, regional, cultural, and religious cleavages in Nigeria. Some perceive it as war by Muslims against Christians, some as a sponsored conspiracy against the Muslim North, and others interpret it as the Northern war against the emergence of President Jonathan from the south-south geopolitical zone. A few regard it as a gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…Apart from the security situation in the North East part of the country, the others reason that advance the postponement was the allegations, counter-allegations on PVCs distributed, it was reported that PVCs had been distributed 80 per cent and above in some Northern states' cities, including those of Boko Haram insurgency torn Northeast, despite huge numbers of displaced persons, while allocation and collection in Southern states' cities, including high-density commercial nerve-centre of Lagos, ranked mostly between 35 and 50 per cent ( Olaniyan & Asuelime, 2015).…”
Section: A Critique Of 2015 Elections In Nigeriamentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the security situation in the North East part of the country, the others reason that advance the postponement was the allegations, counter-allegations on PVCs distributed, it was reported that PVCs had been distributed 80 per cent and above in some Northern states' cities, including those of Boko Haram insurgency torn Northeast, despite huge numbers of displaced persons, while allocation and collection in Southern states' cities, including high-density commercial nerve-centre of Lagos, ranked mostly between 35 and 50 per cent ( Olaniyan & Asuelime, 2015).…”
Section: A Critique Of 2015 Elections In Nigeriamentioning
confidence: 99%
“…The key challenge was that the election was held on the backdrop of the violent insurgency by Boko Haram, a militant group which is particularly affecting the north-eastern part of the country (Olaniyan & Asuelime, 2015). Given the politicisation and manipulation of the upheaval to assume an ethno-regional and religious character, as well as the unprecedented fractionalisation of some elites along these fault lines of identity, the election was seen as the referendum on the survival of the country.…”
Section: A Critique Of 2015 Elections In Nigeriamentioning
confidence: 99%
“…In other words, they are more likely to perceive Boko Haram as a "planned Islamic jihad against Christians in Nigeria." 90 Muslim people (frequently but not exclusively belonging to the Hausa-Fulani group and born in the north), on the other hand, tend to argue more often that unemployment and poverty have caused the uprising. Moreover, they are also the only ones who sometimes indicate that a sense of injustice and the neglect of the northern regions could be a possible cause.…”
Section: Conclusion: Laying Bare Fault Linesmentioning
confidence: 99%
“…Perceptions on the insurgency across Nigeria's disparate nationalities reveal the centrality of "ethno-religious thinking." This has been defined by Olaniyan and Asuelime 93 as "Nigerians' reading of ethnic and religious meanings into most actions in the country"; and Nigerian students clearly read the Boko Haram crisis through such ethno-religious glasses. Public opinion-at least the one held by Nigerian students-is polarized over Boko Haram's agenda, consequences, and solutions; and these polarized perceptions reflect long-standing grievances.…”
Section: Conclusion: Laying Bare Fault Linesmentioning
confidence: 99%
See 1 more Smart Citation